Key drivers of bank financial performance: Insights from the Arab Levant region - Naji Anton Alslaibi; Rasha Qawasmeh; Husni Samara; Rafat Moahmmad Abualrob (Banks and Bank Systems)
This study investigates the key determinants of bank financial performance in the Arab Levant region from 2017 to 2023, focusing on profitability and market valuation, while analyzing internal and external factors, including inflation, capital adequacy, and bank size, amid the unique regional economic dynamics post-Corona Virus Disease in 2019. The study sample comprises 15 Jordanian, 6 Palestinian, 5 Lebanese, and 13 Syrian banks. A descriptive analytical method and STATA were used for the hypothesis testing. The results reveal that inflation, bank type, country, bank size, and capital adequacy positively influence profitability, whereas liquidity ratio negatively affects profitability. Other variables, such as gross domestic product growth rate, country, bank age, operational efficiency, coronavirus, and financial inclusion, have no significant impact on profitability. Additionally, the pandemic and financial inclusion had a statistically negative effect on market valuation, whereas the other variables had no significant influence. This study provides fresh insights into bank performance in the rarely studied Middle Eastern markets by exploring profitability and market valuation within a unique pre- and post-pandemic context, thus enriching our understanding of bank performance in emerging economies. It offers actionable strategies for policymakers and managers to enhance profitability, market value, and resilience by focusing on fintech and equitable financial practices to support societal resilience and economic stability in conflict-affected, emerging economies.